2017
DOI: 10.3389/fpsyg.2017.01687
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults Perceptions of Technology and Barriers to Interacting with Tablet Computers: A Focus Group Study

Abstract: BackgroundNew technologies provide opportunities for the delivery of broad, flexible interventions with older adults. Focus groups were conducted to: (1) understand older adults’ familiarity with, and barriers to, interacting with new technologies and tablets; and (2) utilize user-engagement in refining an intervention protocol.MethodsEighteen older adults (65–76 years old; 83.3% female) who were novice tablet users participated in discussions about their perceptions of and barriers to interacting with tablets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
377
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 610 publications
(463 citation statements)
references
References 26 publications
34
377
2
4
Order By: Relevance
“…Despite this, by one small study of adults aged 65 to 76 years old who were relatively naïve to technology, especially tablets, the participants were eager to adopt the new technology, however, were apprehensive about lack of clarity in instructions and support. Understanding this perception and implementing eCR with this in mind may find increased support in this age group …”
Section: Digital Smartphone and Internet‐based Cardiac Rehabilitatimentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, by one small study of adults aged 65 to 76 years old who were relatively naïve to technology, especially tablets, the participants were eager to adopt the new technology, however, were apprehensive about lack of clarity in instructions and support. Understanding this perception and implementing eCR with this in mind may find increased support in this age group …”
Section: Digital Smartphone and Internet‐based Cardiac Rehabilitatimentioning
confidence: 99%
“…Understanding this perception and implementing eCR with this in mind may find increased support in this age group. 44 6 | OTHER NOVEL METHODS OF CR group. 46 Art in its various forms has also been evaluated as a possible component of cardiovascular rehabilitation.…”
Section: Hbcr With Telephonic Monitoringmentioning
confidence: 99%
“…It is possible that use of an application for tablets is a larger barrier among older patients. However, qualitative studies among older persons have demonstrated that elderly persons often are positive to using tablets and eager to learn, even though cognitive deficits and low self-efficacy may limit the potential for use [47,48].…”
Section: Acceptance Of Use By Patientsmentioning
confidence: 99%
“…Many senior citizens strongly disapprove or cannot use smartphones (Müller et al, 2013) because of the technology barrier.They show skepticism about using technology in general due to age-related (e.g., cognitive decline) as well as technologyrelated (e.g., interface usability) barriers (Vaportzis et al, 2017) or simply the lack of resources (Kaganek et al, 2017) to purchase such devices. Therefore it is important to recognize the PRMs group diversity with regards their technological literacy and the introduction of a variety of map formats from non-interactive hard copy maps through to non-interactive soft copy maps (electronic versions) to those with GIS-type functionality -interactive geovisualisations.…”
Section: Accessibility Map Technology Related Issuesmentioning
confidence: 99%